NAHDLATUL 'ULAMA'S PHILANTHROPY: THE AID FOR STRATEGY EDUCATION FINANCIAL - Aqimi Dinana; Ainur Rahman; Zainal Arifin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
The study aims the strategy for managing ZIS funds (Zakat, Infaq, and Sadaqah) for carried out to finance education in NU CARE-LAZISNU DIY. The research uses observation data collection methods, interviews, literature studies, and media internet information. In-depth interviews take for as primary data sources and online media as secondary data sources. The results show that NU CARE-LAZISNU DIY collects zakat, infaq, and sadaqah with various methods. The manual payment is the NU CARE-LAZISNU DIY office management. The internet system uses kitabisa.com portal. The aid method develops with the following increasingly cellular devices. The interface official NU CARE-LAZISNU DIY portal is the access to calculate zakat in philanthropy. The user of the NU CARE-LAZISNU DIY education is LP Ma'arif NU DIY as a fellow funding from PWNU DIY. However, NU CARE-LAZISNU DIY puts the engagement philanthropy for scholarships apply. The donator put the trust for management aid that is balanced for increasing statistic for aid fundraising zakat philanthropy scholarship education.